Harnessing nanotechnology for stem-cell therapies: revolutionizing neurodegenerative disorder treatments – a state-of-the-art update - Chengebroyen, Neevashini; Seelan, Anmol; Yoonus Thajudeen, Kamal; Alshehri, Saad Ali; Biswas, Aritra; Adur, Israrahmed; Sundararajan, Vino; Lulu Sudhakaran, Sajitha; Singh, Harpreet (Frontiers in Pharmacology, 2025)
Neurodegenerative disorders, marked by the gradual degeneration and dysfunction of neurons, pose substantial clinical challenges due to the paucity of effective therapeutic strategies and the intricate and multifactorial nature of their underlying pathophysiology. On the other hand nanotechnology, Recent advancements in nanotechnology-driven interventions have significantly augmented the therapeutic potential of stem-cell therapies for the treatment of these complex conditions. Critical limitations in current therapeutic approaches have been highlighted, while potential future directions for their therapy have been outlined. Stem cell types—embryonic, induced pluripotent, and adult neural stem cells—are categorized, with a focus on their unique biological properties and therapeutic potentials in addressing neurodegenerative conditions. The role of nanomaterials in augmenting stem cell generation, scaffold fabrication, and targeted delivery mechanisms is examined, with particular emphasis on the capacity of nanotechnology to enhance regenerative processes and neuroprotective interventions. Nanomaterial-conjugated stem cell therapies are specifically addressed, focusing on their applications in neuronal recovery and treatment monitoring. Challenges associated with stem cell therapies, including ethical considerations, immunogenicity, and the necessity for stringent clinical validation, are critically examined. The integration of nanomedicine with stem cell research is proposed as a promising strategy to overcome these challenges and facilitate the development of novel therapeutic approaches. A comprehensive framework for future research is proposed, focusing on the synergistic integration of nanotechnological advancements with stem cell therapies to improve clinical outcomes and drive innovation in the treatment of neurodegenerative disorders. By integrating existing knowledge and highlighting critical gaps, this review seeks to foster continued research and interdisciplinary collaboration, accelerating progress in this rapidly evolving field.